Perceptions on Genetic and Genome Screening among College Students in the Emirates of Abu Dhabi - Habiba Alsafar; Deema Islayem; Reem Almansoori; Tahnoon Alnahyan; Abdulla Alhammadi; Raven Haan; Guan Tay (Dubai Medical Journal, 2021)
Introduction: Genetic testing is playing a greater part in contemporary medical practice. The ability of high throughput and parallel detection of variants that could predict the possibility of developing genetic diseases and to deliver personalized health care for individuals is slowly but most certainly gaining traction. This study was conceived to investigate the knowledge level and degree of awareness among youth in the United Arab Emirates, on the role of genetic testing in society, and the delivery of health care. Methods: Data from individuals were collected, and statistical analyses were performed to assess whether or not there were differences in people’s attitude toward genetic testing, depending on variables such as age, gender, and prior knowledge of genetic testing. Volunteers were recruited at the main campus of Khalifa University in Abu Dhabi via walk-ins to the recruitment desk or via an email which was circulated to both the staff and student population of the university. The survey that was circulated through email was also shared with friends and family, and through social media, to try to capture a larger and more diverse demographic population. Results: Results found that most of the participants were aware of genetic testing and showed a positive attitude toward the technology. However, there was an apparent lack of knowledge and understanding of regarding certain genetic concepts, such as the alternate sources of obtaining genetic information other than blood samples. The mean knowledge score was 6.3 ± 1.9 out of 9, and mean attitude score was 3.6 ± 1.3 out of 6. The main factors that affected knowledge and attitude were gender and prior knowledge of genetic testing. Conclusion: This study used surveys as an effective tool to evaluate the general knowledge of genetic testing of the general public. It is recommended to embed genetic topics in schools and universities to further increase people’s awareness regarding genetic testing.